2020
DOI: 10.3389/fphys.2020.00797
|View full text |Cite
|
Sign up to set email alerts
|

Selective Regional Alteration of the Gut Microbiota by Diet and Antibiotics

Abstract: The small intestinal microbiota has recently been implicated in contributing to metabolic disease. We previously demonstrated that diets rich in saturated milk fat have a particularly strong impact on the small bowel microbiota as opposed to more distal gastrointestinal (GI) regions. However, the impact of antibiotics and diet on the small bowel microbiota has not been clearly demonstrated. Thus, we sought to determine how diet and antibiotics interact in modulating the regional landscape of the gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…ABXs strongly affect microbial diversity and intestinal barrier function, leading to bacterial translocation of live commensal bacteria to the mesenteric lymph nodes (MLNs) (Knoop et al, 2016). A characteristic feature of reduced bacterial load after ABX treatment is cecum enlargement, which characterizes also GF animals (Devkota et al, 2012;Poteres et al, 2020). Analysis of cecum weight 4 days after recovery from ABX treatment revealed a pronounced increase of this parameter, as expected.…”
Section: Administration Of Apyrase-expressing Bacteria Attenuates Int...supporting
confidence: 57%
“…ABXs strongly affect microbial diversity and intestinal barrier function, leading to bacterial translocation of live commensal bacteria to the mesenteric lymph nodes (MLNs) (Knoop et al, 2016). A characteristic feature of reduced bacterial load after ABX treatment is cecum enlargement, which characterizes also GF animals (Devkota et al, 2012;Poteres et al, 2020). Analysis of cecum weight 4 days after recovery from ABX treatment revealed a pronounced increase of this parameter, as expected.…”
Section: Administration Of Apyrase-expressing Bacteria Attenuates Int...supporting
confidence: 57%
“…Specific bacterial strains, such as Clostridium, influence processes underlying intestinal lipid absorption (see section 5.4). Recently, by comparing the effects of diet (high fat versus low fat), broad-spectrum antibiotics and antibiotic cocktails, Poteres et al (2020) showed that antibiotics had an effect on the murine small intestine, caecum and faeces microbiota composition, while diet significantly affected only the jejunum and caecum microbiota, suggesting that diet has a selective regional impact on the gut microbiota [13]. In addition, Turnbaugh et al (2009) showed using humanized mice that switching from a low-fat, plant polysaccharide-rich diet to a high-fat, high-sugar "Western" diet shifts the composition of the microbiota within a single day and changes microbial metabolic pathways and gene expression along the length of the gut, including in the small intestine [116].…”
Section: Impact Of Dietary Lipids On the Bacterial Content In The Jejunummentioning
confidence: 99%
“…Recently, several papers demonstrated the existence of crosstalk among dietary lipids, the jejunum microbiota and the jejunal epithelium [8][9][10][11][12][13]. This review aims to highlight this currently understudied topic and to provide arguments regarding the need for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Through a comparison of the dietary effects, antibiotic cocktails and broad-spectrum antibiotics, Poteres et al. ( Poteres et al., 2020 ) revealed that antibiotics impacted the murine small intestine, faeces and caecum microbiota make-up, whereas dietary intake highly influenced caecum and jejunum microbiota, implying that dietary intake exerts specific and localized effect over gastro-intestinal microbiota. Thus, future exploration on how lipids influence the microbial content in human jejunum is needed to decipher the detailed relationship between microbiota, host, and diet.…”
Section: Physiological Functions Of Fa On Gut Healthmentioning
confidence: 99%